Minimum distance calculation using laser scanner and IMUs for safe human-robot interaction. (August 2019) - Safeea, Mohammad; Neto, Pedro
Highlights: Human pose estimated from laser scanner and IMUs. Human-robot minimum distance calculated from sensor data. Collision avoidance is achieved by adjusting pre-defined robot paths. Real-time collision avoidance with KUKA iiwa robot. Abstract: In this study we investigate the use of a laser scanner/range-finder and inertial measurement units (IMUs) for the application of human-robot interaction in a dynamic environment with moving obstacles/humans. Humans and robots are represented by capsules, allowing to calculate the human-robot minimum distance on-the-fly. A major challenge is to capture the capsules pose. Data from a laser scanner and IMUs attached to the human body are fused to define the torso relative position and the upper body (arms and chest) configuration, respectively. Collision avoidance is achieved with a customized potential field's method that allows to adjust the pre-defined robot paths established off-line while keeping the task target. The proposed framework is validated in real environment using a SICK laser scanner, IMUs and a KUKA iiwa robot. Experiments demonstrated the robustness of the proposed approach in capturing human motion, calculating the human-robot minimum distance and the robot behavior that smoothly avoids collisions with the human.